Level of knowledge on oral health of mothers and their relation to the oral health status of children under five years of age - Benavente Lipa, Lourdes A. (2012)
The aim of this study was to determine the level of knowledge on oral health of mothers and their relationship with oral health status of their children under five years old, who were admitted to hospitals of Ministry of Health (MINSA) and Social Security (ESSALUD). Were taken into consideration ethical standards. This is an analytical and cross-sectional study. The sample consisted of mothers with children under five years of age (n 143). Was used not randomized quota sampling. Was applied a structured questionnaire to collect information about the level of mother´s knowledge on oral health and a diagnostic sheet for oral health status of children under five. Clinical examination was performed with artifitial light, using epidemiological indices: Dental Caries Index (dmft), and the Simplified Oral Hygiene Index by Greene-Vermillion (OHI-S). There was no significant association between level of knowledge on oral health who have mothers with the oral health status of children under five years of age (p 0.16). Mothers had knowledge among regular and good in 77.6 % however this was not reflected in the oral health of children. Was concluded that it should work a program with emphasis on promoting preventive promotional positive attitudes towards oral health care from an early age not only to ensure the spacing of permanent teeth, but also to ensure the child’s feeding and their growth and bio-psycho-social development.